Imitating Quranic sentences as a learning strategy for translating Arabic into Indonesian - Akmaliyah Akmaliyah; Setia Gumilar; Muhammad Ibnu Pamungkas; Irfan Addriadi; Sarastika Endang Hapriyonita; Maman Suherman; Zalifa Nuri (Indonesian Journal of Applied Linguistics, 2023)
Accurately translating the messages embedded in Quranic verses into the target language is of paramount importance. Although numerous studies have examined translation qualities in Quranic translations, there is limited research exploring the effectiveness of an imitation technique in enhancing students' translation skills for Quranic verses into Indonesian. This qualitative descriptive study aims to investigate the efficacy of imitating sentence patterns through the utilization of drill techniques in teaching Arabic-to-Indonesian translation. The study involved a total of 18 students who underwent a pre-treatment translation test and a post-treatment test. The primary focus of the translation assessment centered on accuracy. The findings unveiled that the implementation of this method significantly improved students' translation skills, particularly in terms of accuracy. Not only did it enable students to effectively imitate patterns, but it also fostered creativity by encouraging variations within these patterns while upholding accuracy in conveying the intended meanings from Arabic to Indonesian. The students exhibited enhanced translation quality following the treatment, thus highlighting the positive impact of employing the imitating sentence patterns method. This approach is especially well-suited for beginners as it facilitates the comprehension of fundamental sentence patterns, expands vocabulary, and enhances translation proficiency. When employing this method, it is crucial to consider factors such as using analogous sentence patterns in both languages, avoiding cultural terminology in examples, ensuring literal translations of sentence patterns, and permitting flexibility for variations.